Dihydroazulene-vinylheptafulvene based photoswitchable lewis pairs for tunable H2 activation. (7th June 2019) - Sheikh, Nadeem S.; Hashmi, Muhammad Ali; Munsif, Sajida; Gilani, Mazhar Amjad; Alkhalifah, Mohammed A.; Khan, Afsar; Ayub, Khurshid
Abstract: Photoswitchable catalysis involves alteration in the intrinsic catalytic properties of an active species through a reversible photochemical transformation. Herein, we report dihydroazulene-vinylheptafulvene (DHA-VHF) based photoswitchable frustrated Lewis pairs (FLPs) for reversible hydrogen activation. The dihydroazulene-vinylheptafulvene moieties here do not act as template to control the catalytic activity, rather the core part of the catalyst. The rational design principle involves evaluation of proton and hydride affinities of Lewis acids (borane) and base (phosphine and amine) functionalities installed on dihydroazulene-vinylheptafulvene photoswitch pair. Significant differences are observed between open VHF and closed DHA for proton and hydride affinities, and these differences are explained by geometric and electronic factors. The individual proton and hydride affinities are utilized to logically formulate best relative positions of both Lewis acid and base on a single molecule in order to activate one H2 molecule per photochrome. For our judiciously designed FLPs, the behavior of phosphine based FLP resembles to that of amine based FLPs at position 2 and 3, however they differ at position 8a. For amine based FLP, the energy released for hydrogen splitting is higher than DHA for all positions (2, 3, 8a) whereas in VHF phosphine based FLP, the energy released on H2 splitting in VHF is lower than that of DHA at position 8a. Moreover, hydrogen splitting is studied on couple of cautiously selected molecules based on the proton and hydride affinities. The activation barriers for hydrogen splitting in VHFs are about 8–10 kcal mol −1 lower than the corresponding barriers in DHAs, chiefly due to the higher hydride and proton affinities. Graphical abstract: Image 1 Highlights: The first example of photoswitchable catalysis for tunable H2 activation is reported. The catalyst is rationally designed by studying proton and hydride affinities. Vinylheptafulvene is more reactive for hydrogen activation than dihydroazulene. The energy barriers difference between active and non-active form is 8–10 kcal mol -1 . Phosphine based catalyst offer more selectivity than amine based Lewis pair catalyst.